2019
DOI: 10.1039/c8ra09492f
|View full text |Cite
|
Sign up to set email alerts
|

Structural growth pattern of neutral and negatively charged yttrium-doped silicon clusters YSin0/− (n=6–20): from linked to encapsulated structures

Abstract: A global search for the low energy of neutral and anionic doped Si clusters YSi n 0/À (n ¼ 6-20) was performed using the ABCluster global search technique coupled with a hybrid density functional method (mPW2PLYP). In light of the calculated energies and the measured photoelectron spectroscopy values, the true minima of the most stable structures were confirmed. It is shown that the structural growth pattern of YSi n À (n ¼ 6-20) is from Y-linked two subcluster structure to a Yencapsulated structure in Si cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Yang et al used ABCluster to study metal‐doped silicon clusters MSinq ( q = 0, − 1, n ≤ 20, M = Sc, Y, Ti, Zr, and some lanthanides) [91, 116, 208–220]. The computed photoelectron spectroscopies using GMs agree well with experimental ones.…”
Section: Applicationsmentioning
confidence: 84%
“…Yang et al used ABCluster to study metal‐doped silicon clusters MSinq ( q = 0, − 1, n ≤ 20, M = Sc, Y, Ti, Zr, and some lanthanides) [91, 116, 208–220]. The computed photoelectron spectroscopies using GMs agree well with experimental ones.…”
Section: Applicationsmentioning
confidence: 84%
“…For example, the ground state structures of M@Si 16 (M = transition metal atom including RE metal atom) tend to be fullerene‐like configuration when radii of M are larger than 2.09 Å, but to be Frank‐Kasper (FK) motif when radii of M atom are less than or equal to 2.09 Å. That is, M@Si 16 for M = Y, La‐Lu, Zr, and Hf is fullerene‐like configuration, and that for M = Sc, Ti, and Ta is FK geometry …”
Section: Resultsmentioning
confidence: 99%
“…Most studies have focused on the formation of terbium silicides and have demonstrated that nanoclusters and/or nanowires may play an important role in this physical and chemical process. Correspondingly, nanoclusters have become one of the core issues in the field of nanotechnology owing to their extraordinary structures and properties . On the other hand, the miniaturization of subnano devices could make the cluster assembly change electronic properties by changing shape, size, and composition, but it needs a comprehensive understanding of the interaction between RE atoms and silicon clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is that ABCluster was used to search the GMs of lanthanide (Ln) doped silicon cluster anions as large as LnSi 20 − , and the calculated photoelectron spectroscopy from these GMs agree well with the experimental ones. [21][22][23][24][25][26][27][28][29][30] Another example is that several authors searched the GMs of clusters consisting of atmosphere related molecules like water, ammonia, nitric acid, hydroxymethanesulfonic acid, sulfuric anhydride, and pentoxide−iodic acid. [31][32][33][34][35][36][37][38][39][40][41][42][43] Using GMs of different sizes, atmospheric cluster dynamics equations can be solved 44 and a lot of atmospheric chemical phenomena were successfully explained.…”
Section: Introductionmentioning
confidence: 99%